Impact assessment through microscopic simulation: a sustainable approach to improving traffic congestion - Zhou, Mpumelelo (Department of Civil Engineering, 2025)
This study assesses the changes in travel time patterns on the N2 highway in Cape Town, South Africa. A microsimulation model is developed to analyse average travel times and speeds along the specified route between 2005 and 2023. Historical data is incorporated into the PTV Vissim software, and peak-hour traffic congestion and patterns are investigated. This thesis focuses on the influence of travel time on urban mobility and transport planning. The results reveal the need for innovative solutions to enhance traffic flows along the N2 highway corridor. The introduction provides an overview and sets the context of the study, stipulating the research objectives, scope, and relevance of the research. The methodology details the data collection procedure, model simulation layout, and the approach to assessing travel time patterns. The results section presents a detailed analysis of the PTV Vissim simulation, addressing traffic flow behaviour, peak flow congestion, and the efficiency of the road infrastructure. Research findings are summarised, focusing on areas that require improvements and the advantages of the proposed solutions. The study emphasises the need for innovative and sustainable traffic management strategies. Recommendations detail the requirement to implement enhanced traffic control systems, infrastructure upgrades, and interventions to improve urban mobility and reduce traffic congestion. Ramp metering is investigated as a sustainable approach intervention and the results are discussed. The model predicts that ramp metering techniques could improve highway flows reducing average delays by at least 8%. The model also predicts that congestion charging could improve traffic flows by at least 7%. The conclusion highlights the significance of addressing travel time to create a sustainable and effective transportation network in Cape Town. Future research proposals are suggested, emphasising the necessity for continuous traffic monitoring and adaptive systems to cope with changing traffic patterns. Furthermore, the study underscores the importance of stakeholder engagement in developing and implementing traffic management solutions. Collaborative efforts between government agencies, urban planners, and the community are essential for the success of the proposed interventions.